EVALUASI KEGAGALAN HASIL PRODUKSI MESIN POTONG PLASTIK MENGGUNAKAN METODE DMAIC DI PT. XYZ: Indonesia - Riski Eka Prayoga (Universitas Majalengka, 2023)
The trend of good performance in the manufacturing industry continues to increase in line with high consumer demand. For this reason, the plastic manufacturing industry has to go the extra mile to meet market demand. However, it is constrained by the ability of production machines that risk interfering with product quality. The cutting machine is a plastic production machine at PT. XYZ, functions as a plastic cutter. Has poor performance with high product defects. The research was conducted to determine the factors causing the high product defects on cutting machines at PT. XYZ. This research method uses the DMAIC concept to determine the factors that cause product failure. It was concluded that product failure on cutting machines reached 3422 kg, the DPMO value reached 1335.67 indicating sigma level 4, which means that the quantity of product defects is moderate, the cause of high product defects is due to worn out machine conditions, shortage of spare parts, human error due to workload and lack of supervision. Evaluation and suggestions for minimizing product defects on cutting machines include implementing an apprenticeship system, making SOPs, imposing strict sanctions, tightening supervision, rejuvenating production machines and providing spare parts for production machines. Keywords—Cutting Machine, Defect, DMAIC, Plastic, Quality Control